2021
DOI: 10.1101/2021.11.25.469834
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Increased excursions to functional networks in schizophrenia in the absence of task

Abstract: Brain activity during rest has been demonstrated to evolve through a repertoire of functional connectivity (FC) patterns, whose alterations may provide biomarkers of schizophrenia - a psychotic disorder characterized by dysfunctional brain connectivity. In this study, differences between the dynamic exploration of resting-state networks using functional magnetic resonance imaging (fMRI) data from 71 schizophrenia patients and 74 healthy controls were investigated using a method focusing on the dominant fMRI si… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 38 publications
1
7
0
Order By: Relevance
“…Effect sizes were negligible to small ( d =-0.16 to d =0.36) for early disorder subjects (NAP group) and moderate to large ( d =-0.58 to d =-0.82) for subjects with established schizophrenia (SCHZ group). Previous discrimination analysis on the same Cobre dataset using a distance measure between patterns of instantaneous phase synchrony reported a moderate effect size ( d =0.67) [28], as did another study using the mean probability of dwell time in a global state (Hedge’s g =0.73) [60]. In contrast, one study reported significantly lower effect sizes ( d =0.06 to d =0.31) using measures of metastability in its original form, and using measures of between-network FC ( d =0.04 to d =0.52) [61].…”
Section: Discussionmentioning
confidence: 89%
“…Effect sizes were negligible to small ( d =-0.16 to d =0.36) for early disorder subjects (NAP group) and moderate to large ( d =-0.58 to d =-0.82) for subjects with established schizophrenia (SCHZ group). Previous discrimination analysis on the same Cobre dataset using a distance measure between patterns of instantaneous phase synchrony reported a moderate effect size ( d =0.67) [28], as did another study using the mean probability of dwell time in a global state (Hedge’s g =0.73) [60]. In contrast, one study reported significantly lower effect sizes ( d =0.06 to d =0.31) using measures of metastability in its original form, and using measures of between-network FC ( d =0.04 to d =0.52) [61].…”
Section: Discussionmentioning
confidence: 89%
“…Previous studies applying LEiDA have reported alterations in a "fully connected" brain state, characterized by all elements having the same sign 31,32,39,[42][43][44][45][46] . Here we also observed this fully connected state and report an increase in fractional occurrence significantly associated with SDI, but not PPL.…”
Section: Discussionmentioning
confidence: 97%
“…Previous studies applying LEiDA have reported alterations in a “fully connected” brain state, characterized by all elements having the same sign (Cabral et al, 2017; Escrichs et al, 2021; Farinha et al, 2021; Figueroa et al, 2019; Larabi et al, 2020; Lord et al, 2019; Stark et al, 2021; Vohryzek et al, 2020). Here we also observed this fully connected state and report an increase in fractional occurrence significantly associated with SDI, but not PPL.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have found alterations in GS, although the results are not always consistent. For instance, Farinha et al described decreased GS and increased recruitment of functional networks in schizophrenia (Farinha et al 2022). On the other hand, increased cortical power and variance were observed in two independent samples of patients affected by schizophrenia compared to healthy controls when global signal was not regressed out of the data (Yang et al 2014(Yang et al , 2017.…”
Section: Schizophrenia Is Characterised By Alterations In Functional ...mentioning
confidence: 99%